Analisis Perkembangan Pasar Pariwisata Sebagai Penggerak Ekonomi Kreatif Di Kota Metro (Studi Kasus Di Pasar Yosomulyo Pelangi Dan Wisata Kuliner Jamur Sawah) - Putri, Pramesella; Nusantoro, Jawoto; Darmayanti, Elmira Febri (Universitas Muhammadiyah Metro, 2022)
This research is a qualitative research with a qualitative descriptive method that aims to (1) determine the development of the tourism market in Metro City (2) Analyze the characteristics of the development of Yosomulyo Pelangi Market and Mushroom Sawah Culinary Tourism as a driving force of the creative economy in Metro City. This study took 4 respondents or informants consisting of the initiators and managers of the two tourism markets. Methods of data collection using interview techniques, observation, and documentation. Data analysis techniques consist of data reduction (data reduction), data display (data presentation), and data conclusion drawing/verification (drawing conclusions). Based on the results of the analysis and assessment of this study, it shows that the development of Yosomulyo Pelangi Market and Mushroom Sawah Culinary Tourism as a driving force of the creative economy in Metro City is quite good by proving the percentage results at Yosomulyo Pelangi Market by 95% and Mushroom Sawah Culinary Tourism by 65%. The characteristics of the development of the tourism market in Metro City are the combination of tourism, culinary, market and photos which are managed by empowering the surrounding community.